A golden jewel: first report of golden-haired tube-nosed bat Harpiola isodon (Chiroptera: Vespertilionidae) from India - Saikia, Uttam; Ruedi, Manuel; Chakravarty, Rohit; Kamalakannan, Manokaran; Lyngdoh, Jennifer; Gautam, Amlanjyoti; Goswami, Rajib; Csorba, Gábor (Zootaxa, 2025)
The tube-nosed bat genus Harpiola is represented by two species, the Indian endemic H. grisea and its Indo-Chinese congener H. isodon. Based on morphometric and genetic analyses of a recently captured specimen from Mizoram state in India, we report the first occurrence of H. isodon from India and extend its eastward range by over 1000 km. We provide morphometric data of H. isodon across its distribution range and describe its echolocation call. We also revise the earlier record of H. grisea from Mizoram as H. isodon restricting the former species to the western Himalayan region of India, and draw attention to the rich diversity of bats in the northeastern region of India, requiring an integrative systematics assessment.